The quality of question types in Swedish police interviews with young suspects of serious crimes. (June 2019) - Winerdal, Ulrika; Cederborg, Ann-Christin; Lindholm, Johanna
This study explores how juvenile offenders in Sweden between the age of 15 and 17 are interviewed by police officers when suspected of homicide crimes. The quality of question types was assessed in 47 authentic interviews. The findings show that the police officers used option-posing and suggestive questions most frequently and social pressure was used in three predominating ways: to confront, to challenge and to appeal for a confession. The conclusion is that the police officers' question style to a large extent contradicts recommendations for how to interview children. There is therefore a need to develop an evidence-based interview practice for interviewing young suspects.